Astragalus membranaceus extract reduces functional knee joint pain: a randomized, double-blinded, placebo-controlled trial - Lippi, Lorenzo; Turco, Alessio; Rudrappa, Girish H.; Moalli, Stefano; de Sire, Alessandro; Invernizzi, Marco (Frontiers in Pain Research, 2025)
IntroductionConcerns regarding the side effects of pharmacotherapy in the management of joint pain have led to increased interest in dietary supplements. Astragalus membranaceus root extract (AME) has been proposed as an alternative approach to relieving knee joint pain. The present study evaluated the efficacy and safety of a standardized AME in patients with functional knee joint pain.MethodsA double-blind, randomized controlled trial was conducted with 90 adults (18–60 years of age) from Rajalakshmi Hospital and Research Center, Karnataka, India. Participants were randomly assigned to receive either 480 mg of AME (n = 45) or placebo (n = 45) for 28 days. The primary outcome was knee pain reduction, which was assessed using a visual analog scale (VAS) after a 6-min walk test. Secondary outcomes included the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Stair Climb Test (SCT), knee range of motion (ROM), and treatment compliance, evaluated at baseline and at follow-up on days 5, 14, and 28. Patient satisfaction and safety were also assessed.ResultsThe AME group exhibited a significant 30% reduction in knee pain (p < 0.0001), with mean VAS scores dropping from 6.7 ± 0.5 to 1.2 ± 0.6. Significant improvements were observed in the WOMAC, SCT score, and ROM (p < 0.0001). Patient satisfaction was higher in the active-treatment group, and no serious adverse events were reported.DiscussionAME was a safe and effective alternative for the management of knee joint pain and merits further longer-term investigation. Clinical Trial Registrationhttps://ctri.nic.in/Clinicaltrials/pmaindet2.php?EncHid=OTE3MTU=&Enc=&userName=, identifier CTRI/2023/09/057317.